A resilient column with angular friction damper for seismic performance upgrading of underground structures. (October 2021) - Wang, Yanchao; Chen, Qingjun; Zhao, Zhipeng; He, Zhiming
Highlights: A resilient column with angular friction damper (RC-AFD) for underground structures. Practical design procedure developed for RC-AFD to enable the two-state control. Multiple responses of the central column reduced by isolation effect of RC-AFD. Structural plastic energy dissipation burden significantly relieved by RC-AFD. Structural residual deformation avoided by the self-centering ability of RC-AFD. Abstract: Underground structures can be vulnerable due to seismic-induced deformation. A resilient underground structure is preferable for seismic response mitigation and quick recovery. In this study, a resilient central column with angular friction damper (RC-AFD) was constructed for the seismic performance upgrading of underground structures, and a practical design procedure was developed for the RC-AFD to enable the two-state control for underground structures subject to seismic excitations with multi-intensity. The RC-AFD consists of a self-centering column characterized by relaxed constraints at the top and bottom column that is restricted by unbounded prestressed tendons, whereas a pair of angular friction dampers are placed at the top of the central column. The mechanical model and its physical realization are detailed, whereas the two-state control mechanism is proposed by following the enhanced demand of seismic performance upgrading. The effectiveness and robustness of the proposed RC-AFD for structural seismic response mitigation of typical underground structures were investigated in terms of structural displacement, shear force, bending moments, and energy-based responses. The obtained results show that the two flexible connection joints concentrated at the top and bottom of the RC-AFD produce a significant isolation effect, through which the multiple responses of the central column can be reduced significantly. Benefiting from the two-state design and the employed angular friction damper with a large radius plate, the RC-AFD exhibits an enhanced energy dissipation capacity, which robustly dissipates the intense plastic energy for multi-intensity excitations. As a consequence, the plastic energy dissipation burden of the primary structures can be significantly relieved and residual deformation can be avoided due to the excellent self-centering ability.